MCM-41-anchored sulfonic acid (MCM-41-SO3H): An efficient heterogeneous catalyst for green organic synthesis. Issue 21 (1st November 2016) - Vekariya, Rajesh H.; Prajapati, Neelam P.; Patel, Hitesh D.
ABSTRACT: MCM-41-anchored sulfonic acid (MCM-41-SO3 H) used as a solid acid catalyst has been reported in recent years for various synthetic protocols. The superior advantage of MCM-41-SO3 H is that it can be recovered and reused several times without loss of its efficiency. In this tutorial review, we attempt to give an overview of the use of MCM-41-SO3 H as a solid and heterogeneous catalyst in the synthesis of various organic compounds that have industrial and pharmaceutical applications. GRAPHICAL ABSTRACT: